Distribution of benthic foraminifera in Pahang River Estuary, Malaysia - Noraswana, N.F.; Ramlan, O. (Penerbit Universiti Kebangsaan Malaysia, 2015)
A study on the distribution of benthic foraminifera in surface sediment was carried out along Pahang River Estuary in the east coast of Peninsular Malaysia (South China Sea). A total of 30 sediment samples were taken from the sampling stations between latitude 3°12’ and 3°47’N and longitude 103°24’ and 103°43’E. A total of 22,457 individuals of foraminifera belonging to 30 families, 47 genera and 84 species were identified. The dominant species was Amphistegina lessonii d’Orbigny, 1826 with 4,084 individuals obtained, then followed by Amphistegina gibbosa d’Orbigny, 1839 (3,544 individuals) and Asterorotalia pulchella (d’Orbigny, 1839) (2,010 individuals). Amphisteginidae was the dominant family with 7,628 individuals (representing 33.97% of all individuals). While family with the most diverse species was Hauerinidae with 20 species. The species diversity was from 9 to 42 species. The abundance of benthic foraminifera was from 98 to 3,725 individuals. The species diversity index, H(s) was in the range of 1.41 to 2.96. A comparative analysis showed high degree of resemblance between the study area and southwestern South China Sea.